In vitro assembly of the trehalose bi-enzyme complex with artificial scaffold protein - Wang, Xiangyi; Jiang, Yi; Liu, Hongling; Zhang, Xinyi; Yuan, Haibo; Huang, Di; Wang, Tengfei (Frontiers in Bioengineering and Biotechnology, 2023)
Trehalose is a significant rare sugar known for its stable properties and ability to protect biomolecules from environmental factors. In this study, we present a novel approach utilizing a scaffold protein-mediated assembly method for the formation of a trehalose bi-enzyme complex. This complex consists of maltooligosyltrehalose synthase (MTSase) and maltooligosyltrehalose trehalohydrolase (MTHase), which work in tandem to catalyze the substrate and enhance the overall catalytic efficiency. Utilizing the specific interaction between cohesin-dockerin, this study presents the implementation of an assembly, an analysis of its efficiency, and an exploration of strategies to enhance enzyme utilization through the construction of a bi-enzyme complex under optimal conditions in vitro. Furthermore, the bi-enzyme complex demonstrated a trehalose production level 1.5 times higher than that of the free enzyme mixture at 40 hours, with a sustained upward trend. Compared to free enzyme mixtures, the adoption of a scaffold protein-mediated bi-enzyme complex may improve cascade reactions and catalytic effects, thus presenting promising prospects.